Cardiovascular Associations with Abnormal Brain Magnetic Resonance Imaging in Neonates with Hypoxic Ischemic Encephalopathy Undergoing Therapeutic Hypothermia and Rewarming - More, Kiran S.; Sakhuja, Pankaj; Giesinger, Regan E.; Ting, Joseph Y.; Keyzers, Matthew; Sheth, Jesal N.; Lapointe, Anie; Jain, Amish; Moore, Aideen M.; Miller, Steven P.; McNamara, Patrick J. (American Journal of Perinatology, 2018)
Objective This article compares hemodynamic characteristics of neonates with hypoxic ischemic encephalopathy (HIE) receiving therapeutic hypothermia (TH) with normal versus abnormal brain magnetic resonance imaging (MRI).Methods Serial echocardiography (echo) was performed within 24 hours, after 48 to 72 hours of cooling, within 24 hours of normothermia, and after starting feeds. Pulmonary hemodynamics, cardiac output, and ventricular function were evaluated. All neonates underwent brain MRI (day 4–5), per clinical standard of care. Clinical cardiovascular and echocardiography characteristics were compared between patients with normal versus abnormal MRI. Cardiovascular changes during TH and after rewarming were identified.Results Twenty neonates at median gestation and birth weight of 40 weeks (interquartile range [IQR]: 39, 41) and 3,410 g (IQR: 2,885, 4,093), respectively, were enrolled. Increased median left ventricular output (LVO) (106–159 mL/kg/min, p < 0.001) and reduced isovolumic relaxation time (IVRT) (48–42 ms, p < 0.001) were seen after rewarming. Echocardiography evidence of pulmonary hypertension (PH) was identified in five neonates. Eight neonates (40%) had brain injury identified on MRI (watershed [n = 4], basal ganglia [n = 4]); this subgroup were more likely to have echo evidence of PH at 24 hours.Conclusion Longitudinal changes in cardiac output were noted in neonates with HIE during TH and rewarming. Echocardiography evidence of PH, however, was associated with abnormal MRI brain. The prognostic relevance of these physiologic changes requires more comprehensive delineation.
Keywords: hypoxic ischemic encephalopathy; therapeutic hypothermia; myocardial performance and hemodynamics